2002
DOI: 10.2337/diabetes.51.5.1337
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Acute and Chronic Administration of the Melanocortin Agonist MTII in Mice With Diet-Induced Obesity

Abstract: High-fat diet-induced obesity (DIO) in rodents is associated with hyperleptinemia and resistance to leptin, but the response to agents acting downstream of leptin receptors remains unknown. We assessed the response of mice with DIO to treatment with MTII, an ␣-melanocyte-stimulating hormone analog. MTII delivered four times daily by intraperitoneal injection to C57BL/6J mice produced a dose-responsive effect on food intake, body weight, leptin, corticosterone, insulin, and free fatty acids. In DIO mice, admini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

22
158
2
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(183 citation statements)
references
References 55 publications
22
158
2
1
Order By: Relevance
“…Although lacking direct evidence of whole-body energy expenditure, we suggest that, in addition to the hypophagia, an increase in energy expenditure, such as fat oxidation within brown adipose tissue, white adipose tissue or muscle, contributed to the amelioration of body weight and fat in aged obese rats following central Pomc gene therapy and, in particular, was instrumental in maintaining the lost weight after the anorexia attenuated. Second, although the 19-day anorexic response to Pomc gene delivery attenuated, the onset of this tachyphylaxis to central Pomc gene delivery was markedly delayed compared with attenuation of the anorexic response following pharmacological administration of α-MSH or MTII in either normal or dietary obese mice and rats [20,21]. The suppression of food consumption lasted no longer than 4 days in any of these latter studies.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Although lacking direct evidence of whole-body energy expenditure, we suggest that, in addition to the hypophagia, an increase in energy expenditure, such as fat oxidation within brown adipose tissue, white adipose tissue or muscle, contributed to the amelioration of body weight and fat in aged obese rats following central Pomc gene therapy and, in particular, was instrumental in maintaining the lost weight after the anorexia attenuated. Second, although the 19-day anorexic response to Pomc gene delivery attenuated, the onset of this tachyphylaxis to central Pomc gene delivery was markedly delayed compared with attenuation of the anorexic response following pharmacological administration of α-MSH or MTII in either normal or dietary obese mice and rats [20,21]. The suppression of food consumption lasted no longer than 4 days in any of these latter studies.…”
Section: Discussionmentioning
confidence: 83%
“…F344/BN rats also display age-associated impairments in glucose metabolism and insulin responsiveness [18]. Although chronic pharmacological treatment of melanocortin agonists in rodents, including aged rats, reduces food intake and increases energy expenditure, its effectiveness is limited by the rapid tachyphylaxis of the melanocortin responses [19][20][21]. On the other hand, we have demonstrated previously that Pomc gene delivery mediated by recombinant adenoassociated virus (rAAV) elicited a sustained anorexic response (up to 38 days) in obese Zucker rats with defective leptin receptors [22].…”
Section: Introductionmentioning
confidence: 99%
“…injection and peripheral injection (at much higher amounts when calculated as micrograms per animal), suggests that the main site of action of MT-II is the brain (Murphy et al 2000, Azzara et al 2002, Moran et al 2002, Pierroz et al 2002, Bellinger et al 2003, Choi et al 2003, Hansen et al 2005, but some contradictory results in rodent suggested that MT-II does not cross the blood-brain barrier (Trivedi et al 2003). Taking this into account and the wide peripheral tissue specificity of expression of MC3R and MC4R in chickens , we cannot exclude the possibility that the injected MT-II operated through peripheral receptors.…”
Section: Discussionmentioning
confidence: 97%
“…In all genetically and experimentally obese rodent models (except those mutated in MC4R; Marsh et al 1999), MT-II has been shown to be as effective in attenuating food intake as in control mice (Fan et al 1997, Hohmann et al 2000, Pierroz et al 2002. Moreover, consistent with our finding of a longer period of MT-II effectiveness in broilers, similar results were reported in a model of obesity in rats, in which a longer persistence of the anorectic effect of MT-II treatment was observed in leptin-induced, leptin-resistant rats compared with control lean rats (Scarpace et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…We did not find any changes in either basal or glucose-or arginine-induced insulin release in isolated ERKO mouse islets. Importantly, obese mice fed a high-fat diet maintained normoglycaemia by increasing insulin levels when compared with mice fed a low-fat diet [22]. Hence, the absence of increased glucose-stimulated insulin secretion in the presence of insulin resistance might suggest an islet dysfunction in vivo in ERKO mice.…”
Section: Discussionmentioning
confidence: 98%